03 RESPON PETANI TERHADAP PENGGUNAAN COMBINE HARVESTER DI DESA BONTO MARANNU KECAMATAN LAU KABUPATEN MAROS - Jurnal Agribis; Muh. Anas; Mohammad Anwar Sadat; Azisah Azisah (Jurnal Agribis, 2020)
The purpose of this study was to determine the level of response of farmers to the use of Combine Harvester in Bonto Marannu Village, Lau District, Maros Regency. And what factors influence farmers' responses to the use of Combine Harvester in Bonto Marannu Village, Lau District, Maros Regency. This research is located in the Village of Bonto Marannu, District of Lau, Maros Regency. Total population of farmers (respondents) is 30 people, where rice farmers who have 0.5 ha of land area are 6 people, land area of 1 ha 9 people, 1.5 ha 7 people, 2 ha 5 people and land area of 2.5 ha is 3 people. The results showed that the response of farmers to the use of a combined harvester machine in Lau sub-district of Maros Regency was included in the high category based on indicators of attitudes, knowledge and behavior of farmers towards the use of a combine harvester machine. And the factors that significantly influence the response of farmers to the use of a combine harvester machine are attitude, knowledge and behavior.